ANALYSIS OF ECOLOGICAL-GEOGRAPHICAL FEATURES OF THE FAUNA SCARAB BEETLES (COLEOPTERA: SCARABAEOIDEA) OF THE SOUTH RUSSIA - I. B. Shokhin (Юг России: экология, развитие, 2014)
Ecological-geographical characteristics of the 292 species and 17 subspecies of lamellicorn beetles of the south of Russia are consi-dered. 3 zoogeographical complexes with 6 groups and 7 subgroups of an area are discharged; 2 ecological groups with 7 basic com-plexes; 4 groups in relation to humidity. Distribution of the lamellicorn beetles in 15 physiographic areas are tracked: 3 basic groups of areas are discharged, conterminous to three basic zoogeographical groups of Tethis complex (Setian, Scythian and Mediterranean). The zoogeographical analysis of the fauna of lamellicorn beetles of region with the count of discharged areas are given.